Application of whole genome sequencing in tuberculosis clinical trials - Gillespie, Stephen (Henry Stewart Talks, 2021)
Introduction to tuberculosis clinical trials and M. tuberculosis typing, Understanding mixed infections and their impact on clinical trials, How to distinguish relapse from reinfection and to determine emergent resistant strains, How to establish such methods in the context of trials, outlining the challenges that are still to be overcome